La experiencia de la creación artística: el creador y la fantasía - Mancilla, Lucía (2024)
This work explores, from a Husserlian perspective, the experience of artistic creation. Thus, it starts from his analyses on the internal time consciousness in order to delve into the constituent phenomena that operate both actively and passively in the creative act. This return to the anonymous depths of consciousness allows us to reflect on the original character of the present within a temporal horizon and, with it, a form of responsibility of the artist regarding his own time. Finally, Husserl’s conception of fantasy will be explained as a type of peculiar experience that, unlike image consciousness, neutralizes reality to open its own horizon that is able to confront us.